Assessment of human faecal contamination on groundwater quality and reporting consequent waterborne diseases in Funtua Metropolis, Katsina State, Nigeria - Odewade, L. O.; Imam, A. A.; Adesakin, T. A.; Odewade, J. O. (Frontiers in Water, 2025)
This study assessed the impact of seepage from pit latrines on groundwater quality and the prevalence of waterborne diseases in primary health care in Funtua town, Katsina State, Nigeria. Well water samples were collected from 15 different areas in 8 out of the 11 wards within Funtua Local Government, while three wards were excluded due to no record of the chlorella outbreak. Water samples were collected twice for each season (dry and wet) from the 15 sampling locations throughout the study area and transported immediately to the laboratory for analysis. The samples were analyzed according to the standard methods and procedures of APHA (2005). Most of the physicochemical parameter results fell within the limits established by WHO (2011) and NSDWQ (2015), except for dissolved oxygen (DO), chloride, total dissolved solids (TDS), and electrical conductivity (EC). The maximum mean concentrations of pH, phosphate, and sulphate (7.64 ± 0.54, 19.23 ± 4.63 mg/L, and 1.12 ± 0.64 mg/L) were recorded in Danduste ward, while a low turbidity mean value of 2.96 ± 0.31 NTU was observed in Goya ward. The high total coliform and faecal coliform counts were recorded from well water samples in all the wards, while Escherichia coli, Shigella dysenteriae, and Salmonella typhi were the bacterial isolates identified during this study. Diarrhoea, typhoid, and dysentery were the most commonly reported waterborne diseases in most primary health centers within this study area. The study revealed that well water sources were located close to pit latrines, averaging 11.4 m, which is below the WHO-recommended safe distance of 30 m. The quality of well water in the Funtua Local Government Area has been compromised due to the proximity of some water sources to pit latrines, rendering the water unsuitable for use without prior treatment.